Формування іншомовної комунікативної компетентності студентів у процесі вивчення іноземної мови - Лозинська Людмила; Lozynska Liudmyla; Курах Наталія; Kurakh Natalia; Депчинська Іветта; Depchynska Ivetta; Depcsinszka Ivett (Видавничий дім «Гельветика», 2022)
Abstract. The article examines the content and features of the formation of students' foreign language communicative competence in the process of learning a foreign language. It has been proven that in the century of globalization and integration, knowledge of foreign languages ​​plays one of the important roles in professional and personal growth. Foreign language communicative competence includes not only the use of basic vocabulary, but also knowledge of professional colloquial phrases, ideas about culture, laws and behavior of other peoples. This is especially relevant in modern society, which at present is much more mobile and has international contacts at all levels. Foreign languages ​​have the ability to develop thinking, to raise both the educational and cultural level of students. The work analyzes the content of the concepts of "competence" and "foreign language communicative competence". Three key components of foreign language communication are singled out competencies, in particular, gnostic, communicative and emotional. It is proved that under foreign language communicative competence should be understood as a special kind of professional competences; ability and readiness to acquire subject, scientific knowledge in professional communication in a foreign language.

Резюме. У статті розглянуто зміст та особливості формування іншомовної комунікативної компетентності студентів в процесі вивчення іноземної мови. Доведено, що в столітті глобалізації та інтеграції одну з важливих ролей в професійному та особистісному зростанні відіграє знання іноземних мов. Іншомовна комунікативна компетентність включає в себе не тільки використання базової лексики, але й знання професійних розмовних фраз, уявлення про культуру, закони та поведінку інших народів. Це має особливу актуальність в сучасному суспільстві, яке на даний час є значно мобільнішим та має міжнародні контакти всіх рівнів. Іноземні мови мають здатність розвивати мислення, підвищувати як освітній, так і культурний рівень студентів. В роботі проаналізовано зміст понять «компетентність» та «іншомовна комунікативна компетентність». Виокремлено три ключових компоненти іншомовної комунікативної компетентності, зокрема, гностичний, комунікативний та емоційний. Доведено, що під іншомовною комунікативною компетентністю потрібно розуміти особливий вид професійних компетентностей; здатність й готовність до набуття предметних, наукових знань в професійному спілкуванні іноземною мовою.

A cikk az idegen nyelvi kommunikatív kompetencia kialakításának tartalmát és jellemzőit vizsgálja az idegennyelv-tanulási folyamatban részt vevő diákok körében. Bebizonyosodott, hogy a globalizáció és az integráció századában a szakmai és személyes fejlődésben az egyik fontos szerepet az idegen nyelvek ismerete tölti be. Külföldi A nyelvi kommunikációs kompetencia nemcsak az alapszókincs használatát foglalja magában, hanem a szakmai ismereteket is köznyelvi kifejezések, gondolatok más népek kultúrájáról, törvényeiről és viselkedéséről.
Formation of foreign language communicative competence of students in the process of foreign language learning
The article considers the content and features of the formation of foreign language communicative competence of students in the process of learning a foreign language. It is proved that in the century of globalization and integration one of the important roles in professional and personal growth is played by knowledge of foreign languages. Foreign language communicative competence includes not only the use of basic vocabulary, but also knowledge of professional colloquial phrases, ideas about the culture, laws and behavior of other peoples. This is especially relevant in modern society, which is currently much more mobile and has international contacts at all levels. Foreign languages have the ability to develop thinking, raise both the educational and cultural level of students. The content of the concepts "competence" and "foreign language communicative competence" is analyzed in the work. Three key components of foreign language communicative competence have been identified, in particular, gnostic, communicative and emotional. It is proved that foreign language communicative competence should be understood as a special type of professional competences; ability and readiness to acquire subject, scientific knowledge in professional communication in a foreign language.
Keywords: компетентність; іншомовна комунікативна компетентність; професійна компетентність; іноземна мова